Penurunan Kadar Oksalat Pati Talas Beneng (Xanthosoma undipes K. Koch) pada Berbagai Konsentrasi NaCl dan Lama Perendaman - Agustin, Nur Aini; Indriyani Syafutri, Merynda; Yanuriati, Anny; Malahayati, Nura; Aryani, Desi; Airlangga, Trubus (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Agustin NA, Syafutri MI, Yanuriati A, Malahayati N, Aryani D, Airlangga T. 2022. Decreasing oxalate levels of taro beneng (Xanthosoma undipes K. Koch) starch at various NaCl concentrations and soaking time. In: Herlinda S. et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 199-207. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Starch is a group of polysaccharides composed of amylose and amylopectin. Taro beneng (Xanthosoma undipes K. Koch) is one of local commodity tubers that has the potential to be used as starch. The problem with taro beneng is content of oxalate which is in water soluble (oxalic acid) and insoluble (calcium oxalate) forms. This study aimed to determine the effect of NaCl concentrations and soaking time on reducing oxalate levels and oxalate reduction values of taro beneng starch. This study used a Factorial Completely Randomized Design (CRD) with two treatment factors, namely NaCl concentrations (5%; 7.5% and 10%) and soaking time (30 minutes; 60 minutes and 90 minutes). The results showed that the difference in NaCl concentrations and soaking time had significant effect on the decrease in oxalate levels and the increase in oxalate reduction values of taro beneng starch. Taro beneng starch soaked for 90 minutes in 10% NaCl solution was the best treatment, because it had the lowest oxalate level (2700 ppm) and the highest reduction value (93.18%).